Participation of Village Health Volunteers in Oral Health Promotion, Pho Thale District, Phichit Province - ใหญ่เจริญ, ธัญญาภรณ์ (Journal of Health Science of Thailand, 2022)
This research is a cross-sectional research. The objectives of this study were to study the participation and related factors of village health volunteers (VHVs) in oral health promotion. The study population was 1,758 volunteers in 11 sub-districts, 97 villages of Pho Thale District, Phichit Province. The sample group was calculated to be 330; and the volunteers were randomly sampled from each village, 3-4 people in each group. Data were collected by self-administered questionnaires between March and April 2021, and were analyzed by descriptive statistics, Pearson correlation and chi-square test at 0.05 significance level. The results showed that most of the samples were female, 77.97%, average age was 51.95 years (SD=11.11), graduated primary school (47.27%), and maried (74.85%). The main occupation was farmers, 63.64%, having average monthly income of 4,114.24 baht per month (SD=2,561.46); and the average duration of working for the VHV was 13.15 years (SD=9.07). The overall level of VHV knowledge was high, with the mean score of 16.08 points (SD=2.22). Attitude level towards oral health promotion was positive, with an average score of 44.70 points (SD=4.51). The level of participation in oral health promotion work was high, with an average score of 57.53 (SD=7.57).There was high level participation in all aspects in the following order: benefit participation (Mean=3.11, SD=0.46), decision-making participation (Mean=2.91, SD=0.55), participation in assessment (Mean=2.84, SD=0.60), and participation in sacrifice, development and practice (Mean=2.67, SD=0.31). The factors associated with VHV’s participation in oral health promotion were work attitude (r=0.14, p=0.01) and age (r=0.23, p=0.01). To encourage VHVs to increase participation in oral health promotion, the oral health work should be integrated with mother and childhealth, elderlycare, or health promotion work in the community in order to prevent the VHVs’ feeling of over-burden beyond their routine job. In addition, concerned agencies should continuously support and promote the work of the VHV in oral health care in the responsible area.